Analyzing business process management capabilities of low‐code development platforms. (8th December 2022) - Sahay, Apurvanand; Di Ruscio, Davide; Iovino, Ludovico; Pierantonio, Alfonso
Abstract: Low‐code development platforms (LCDPs) aim to simplify software systems' development by providing easy‐to‐use graphical interfaces and drag‐and‐drop facilities. The system behaviors are defined through available data handling and workflow mechanisms enabling the specification of business processes from users that do not have strong programming skills. However, the number of LCDPs has grown significantly over the last few years. Consequently, it is not easy for inexpert users to understand their differences, especially in terms of provided modeling constructs. In this article, we analyze and compare eight low‐code development platforms by focusing on their capabilities for specifying business processes. The analysis exploits business process modeling and notation (BPMN) as a reference modeling language. Thus, the core elements of BPMN are leveraged to analyze the workflow mechanisms provided by each of the analyzed LCDP. The article explains different types of process flows and data handling means of the different LCDPs aiming to give potential users objective elements that can be used to make educated decisions when selecting LCDPs.